ENLIGHTENED YOUTH - DEVELOPMENT CRITERIA - Norqulov Uchqun Munavvarovich; Baratov Norjigit Umurovich; Norqulova Lobar Uchqunovna; Savurov Mexroj Toshpo’latovich (Scholar Express Journal, 2023)
The main link of the continuous education system introduced in our republic, the organization of the educational process and its use in higher education institutions responsible for the quality and efficiency of personnel training is one of the priority tasks of every pedagogue. Also, opinions on the formation and development of professional training for students of higher educational institutions, a systematic, comprehensive approach to this process are expressed
Keywords: national independence ideology; socio-economic conditions; high spiritual and moral qualities; pedagogical technologies